New Adaptive Data Transmission Scheme Over HF Radio - Salim, Khalifa Abboud; R. Kadhim, Abdul-Karim A.; Ahmad, Adil H. (Al-Khwarizmi Engineering Journal, 2008)
Acceptable Bit Error rate can be maintained by adapting some of the design parameters such as modulation, symbol rate, constellation size, and transmit power according to the channel state.An estimate of HF propagation effects can be used to design an adaptive data transmission system over HF link. The proposed system combines the well known Automatic Link Establishment (ALE) together with variable rate transmission system. The standard ALE is modified to suite the required goal of selecting the best carrier frequency (channel) for a given transmission. This is based on measuring SINAD (Signal plus Noise plus Distortion to Noise plus Distortion), RSL (Received Signal Level), multipath phase distortion and BER (Bit Error Rate) for each channel in the frequency list. Channel condition evaluation is done by two arrangements. In the first an FFT analysis is used where a pilot signal is transmitted over the channel, while the data itself is used in the second arrangement. Passive channel assessment is used to avoid bad channels hence limiting the frequency pool size to be used in the point to point communication and the time required for  scanning and linking. An exchange of channel information between the transmitting and receiving stations is considered to select the modulation scheme for transmission. Mainly MPSK and MFSK are considered with different levels giving different data rate according to the channel condition. The results of the computer simulation have shown that when transmitting at a fixed channel symbol rate of 1200 symbol/sec, the information rate ranges from 2400 bps using 4FSK up to 3600 bps using 8PSK for SNR ranges from 11dB up to 26dB.